Using rapid game design in Zambia - International Water Management Institute (International Water Management Institute, 2024)
In the context of the Lower Kafue Basin, RGD offers a novel and engaging approach to multistakeholder dialogue by harnessing the power of gamification of complex issues. The game designing process unravels waterscape and landscape issues through interactive stakeholder experiences that encourage inclusive collaboration, problem-solving and empathy while breaking down sectoral barriers and fostering understanding between stakeholders about common concerns.